Proceedings of the 14th ACM International Conference on Mobile Computing and Networking 2008
DOI: 10.1145/1409944.1409959
|View full text |Cite
|
Sign up to set email alerts
|

Wireless device identification with radiometric signatures

Abstract: We design, implement, and evaluate a technique to identify the source network interface card (NIC) of an IEEE 802.11 frame through passive radio-frequency analysis. This technique, called PARADIS, leverages minute imperfections of transmitter hardware that are acquired at manufacture and are present even in otherwise identical NICs. These imperfections are transmitter-specific and manifest themselves as artifacts of the emitted signals. In PARADIS, we measure differentiating artifacts of individual wireless fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
456
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 708 publications
(459 citation statements)
references
References 15 publications
1
456
0
2
Order By: Relevance
“…Besides the mentioned works on UHF RFID tags, physical-layer fingerprinting has been explored on different platforms such as VHF [10,30,32], Bluetooth [15], IEEE 802.11 [5,14,16,33], IEEE 802.15.4 (ZigBee) [7,24], and GSM [25,26]. Physical-layer identification has also been considered for inductive coupled HF RFID devices [6,27,28], especially for detecting cloned or counterfeit HF RFID smart cards and electronic passports.…”
Section: Rfid Fingerprinter Requirementsmentioning
confidence: 99%
“…Besides the mentioned works on UHF RFID tags, physical-layer fingerprinting has been explored on different platforms such as VHF [10,30,32], Bluetooth [15], IEEE 802.11 [5,14,16,33], IEEE 802.15.4 (ZigBee) [7,24], and GSM [25,26]. Physical-layer identification has also been considered for inductive coupled HF RFID devices [6,27,28], especially for detecting cloned or counterfeit HF RFID smart cards and electronic passports.…”
Section: Rfid Fingerprinter Requirementsmentioning
confidence: 99%
“…Inversion for the case when ∕ = is obtainable via a number of methods such as the pseudoinverse, however this topic is beyond the scope of this paper . An estimate for the intrinsic channel responseĤ[ 0 ] is produced via (10), and thus the data signal can be recovered by pre-multiplying (13) by the inverse of the normalized channel estimate produced by the MMSE estimator, orĤ…”
Section: A Data Recoverymentioning
confidence: 99%
“…A further advantage to the proposed system is that channel estimates obtained during (10) and (11), and subsequent channel equalization steps preformed in (15) and (17) are identical steps taken by an unmodified/unaware receiver. Thus, we have demonstrated that the fingerprinted signal is received by unaware receivers without modification to the receiver, channel estimation procedure, or equalization device when generalized pilot embedding and channel estimation are employed.…”
Section: A Data Recoverymentioning
confidence: 99%
See 2 more Smart Citations